KAJIAN NUTRITIF PELET DENGAN PENAMBAHAN TEPUNG DAUN KELOR (MORINGA OLEIFERA): NUTRITIONAL STUDY OF PELLETS WITH THE ADDITION OF MORINGA LEAF FLOUR - Afdahla, Virkantyas; Sariri, Ahimsa Kandi (Universitas Boyolali, 2025)
This study aims to determine the content of dry matter, crude fiber and crude protein content of pellets supplement with moringa leaf flour. The study was conducted over five months period at the Microbiology Laboratory, Faculty of Agriculture, Bangun Nusantara University, Sukoharjo and the Laboratory of the Faculty of Animal Husbandry, Diponegoro University. The study was conducted through three main stages, preparation, mixing and pellet molding. The purpose of this study was to identify the dry matter, crude fiber and crude protein content of pellets supplemented with moringa leaf flour. The results of this study had a significant effect on the dry matter content but did not significantly affect the crude fiber and crude protein content of pellets supplemented with moringa leaf flour.